Challenges and opportunities in improving the production of bio-ethanol. (April 2015) - Baeyens, Jan; Kang, Qian; Appels, Lise; Dewil, Raf; Lv, Yongqin; Tan, Tianwei
Abstract: Bio-ethanol, as a clean and renewable fuel, is gaining increasing attention, mostly through its major environmental benefits. It can be produced from different kinds of renewable feedstock such as e.g. sugar cane, corn, wheat, cassava (first generation), cellulose biomass (second generation) and algal biomass (third generation). The conversion pathways for the production of bio-ethanol from disaccharides, from starches, and from lignocellulosic biomass are examined. The common processing routes are described, with their mass and energy balances, and assessed by comparing field data and simulations. Improvements through 5 possible interventions are discussed, being (i) an integrated energy-pinch of condensers and reboilers in the bio-ethanol distillation train; (ii) the use of Very High Gravity (VHG) fermentation; (iii) the current development of hybrid processes using pervaporation membranes; (iv) the substitution of current ethanol dewatering processes to >99.5 wt% pure ethanol by membrane technology; and (v) additional developments to improve the plant operation such as the use of microfiltration of the fermenter broth to protect heat exchangers and distillation columns against fouling, or novel distillation concepts. Whereas the benefits of introducing these techniques are recognized, extensive research is still needed to scientifically and economically justify their application. The paper finally presents a tentative economic assessment, with production costs not only depending on the extent of applying process improvements, but also on the raw material used in the process.